Protest Song and Verse in Cape Breton Island - MacKinnon, Richard (Ethnologies, 2008)
On Cape Breton Island, where coal mining and steel making were once an essential part of the region’s culture and economy, protest song and verse are found in abundance. This article explores some previously unexamined protest songs and verses of Cape Breton Island. The body of songs is culled largely from the Maritime Labour Herald, a newspaper of the 1920s that included both locally and internationally composed works. Some earlier folklorists ignored protest songs because their paradigms did not permit them to view these forms as authentic cultural expressions. Their approach raises complex issues of how authenticity is constructed and by whom. My intent is to show that a well-developed protest song tradition was alive and well, and played an important role in the labour struggles of the 1920s. Indeed, these vernacular materials were used for solidarity during times of upheaval and change in Cape Breton Island.